2004
DOI: 10.1021/la0496486
|View full text |Cite
|
Sign up to set email alerts
|

UV Causes Dramatic Changes in Aggregation with Mixtures of Photoactive and Inert Surfactants

Abstract: Aqueous mixtures of photosensitive and inert surfactants have been prepared; photoreactions and changes in aggregation after irradiation have been characterized. The photosensitive component was a stilbene-containing gemini photosurfactant (E-SGP), and the inert surfactants were either DTAB (dodecyltrimethylammonium bromide) or one of two different gemini surfactants, 12-4-12 or 16-4-16 (butanediyl-1,4-bis(dodecyldimethylammonium bromide) or butanediyl-1,4-bis(hexadecyldimethylammonium bromide)). Small-angle n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…[15][16][17][18]). Following standard procedures, raw data were treated to yield normalized scattering intensities I (Q) in cm −1 , where the momentum transfer Q = (4π/λ) sin(θ/2), with θ the scattering angle.…”
Section: Apparatusmentioning
confidence: 99%
“…[15][16][17][18]). Following standard procedures, raw data were treated to yield normalized scattering intensities I (Q) in cm −1 , where the momentum transfer Q = (4π/λ) sin(θ/2), with θ the scattering angle.…”
Section: Apparatusmentioning
confidence: 99%
“…The phase and structural studies of AOT-stabilized water-inoil microemulsions have been extensively reviewed [8]. Over the years there have been numerous studies of aggregation in microemulsion systems [9][10][11][12][13][14][15][16][17][18][19]. The approaches explored have ranged from pressure [9] and temperature [9,10] variation, electric field effects [11], to addition of various kinds of additives [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The approaches explored have ranged from pressure [9] and temperature [9,10] variation, electric field effects [11], to addition of various kinds of additives [12][13][14][15][16]. Photosensitive surfactants have been used [17][18][19], to demonstrate aggregation and phase destabilization induced by UV light. As far as is known there is no report of solvent-induced aggregation in microemulsion systems, employing blends of good and bad solvents.…”
Section: Introductionmentioning
confidence: 99%
“…While after UV irradiation, the effective domain size detected by DLS increases from 73 to 137 nm, this final state is still smaller than the original size (197 nm). On the basis of photochemical studies [15][16][17][18][19], the post-irradiation structures consist of mixed block co-polymer/hexylbenzene/hexylphenol/sodium hydrogen sulfate aggregates, where hexylbenzene is the dominant photoproduct. Thus, after irradiation the average domain size of L α -B might be expected to differ from the original L α -A phase.…”
Section: Saxs and Sansmentioning
confidence: 99%
“…This electrostatic effect can be eliminated by changing the ionic strength of the solution, through adding inert electrolyte. Recently, light has been used as a method to control vesicle stability [14][15][16][17][18]; this is an attractive approach because it is not necessary to change thermodynamic variables or the system chemical composition. Extensive studies involving an anionic photolyzable surfactant, sodium 4-hexylphenylazosulfonate (C 6 PAS), showed that UV light can provoke the breakdown of microemulsions formulated from mixtures with inert Aerosol-OT [19,20].…”
Section: Introductionmentioning
confidence: 99%